Bleeding patterns after vaginal misoprostol for treatment of early pregnancy failure - Davis, A.R.; Robilotto, C.M.; Westhoff, C.L.; Forman, S.; Zhang, J. (Human reproduction (Oxford), 2004)
BACKGROUND: Dilatation and curettage (D&C) has been the usual treatment for early pregnancy failure (EPF). Medical management with misoprostol may be an effective alternative. Bleeding patterns during and after medical management of EPF are unknown. METHODS: A prospective cohort study was conducted at University‐based clinics and physician offices. Eighty women <11 weeks estimated gestational age with a diagnosis of missed abortion or fetal demise were enrolled. Treatment consisted of either 800 µg of moistened (2 ml of saline) or dry vaginal misoprostol. Self‐reported bleeding and sanitary product usage were recorded in a daily 2 week diary. Haemoglobin was assessed at enrolment and 2 weeks later. RESULTS: After misoprostol treatment, patients reported bleeding or spotting every day for the 14 days observed. Self‐assessed heavy bleeding days were few (median 3) and usually occurred immediately after treatment. Sanitary pad use was highly variable (mean 30.5, range 2–125 pads over the 2 week period) and not related to changes in haemoglobin. The mean decrease in haemoglobin was 0.5 g/dl (SD 1.2). Complete expulsion without D&C occurred in 85% of subjects. CONCLUSIONS: Bleeding for at least 2 weeks after vaginal misoprostol for EPF is common. Heavy bleeding is usually limited to a few days after treatment. Clinically important changes in haemoglobin are rare.